Efficacy of herbal medicine TJ-14 for acute radiation-induced enteritis: a multi-institutional prospective Phase II trial. (6th November 2019) - Murai, Taro; Matsuo, Masayuki; Tanaka, Hidekazu; Manabe, Yoshihiko; Takaoka, Taiki; Hachiya, Kae; Yamaguchi, Takahiro; Otsuka, Shinya; Shibamoto, Yuta
Abstract: The purpose of this multi-institutional Phase II trial study was to prospectively investigate the efficacy of the herbal medicine TJ-14 for acute radiation-induced enteritis (ARE). TJ-14 was administered orally as a first-line treatment for ARE. The primary end point was efficacy at 1 week. The secondary end points were: (i) the efficacy of TJ-14 at 2 and 3 weeks after its administration, (ii) the quality of life score (FACT-G) at 1, 2 and 3 weeks after its administration, and (iii) adverse events. If the efficacy of TJ-14 was observed in eight patients or fewer, its efficacy was rejected. Results: Forty patients receiving pelvic radiotherapy were enrolled. Of these, 22 developed ARE and received TJ-14. Among these, 19 had cervical cancer and 9 received chemoradiotherapy. TJ-14 efficacy was shown in 19 out of the 22 patients (86%). Stool frequency per day at 1 week significantly decreased (mean ± SD: 4.9 ± 2.1 vs 3.7 ± 1.9, P = 0.02). This effect continued at 2 (2.2 ± 1.4, P = 0.004) and 3 weeks (2.1 ± 0.9, P = 0.05). Thirteen out of the 22 patients (59%) continued TJ-14 until the end of radiotherapy. FACT-G score deterioration was not observed after the administration of TJ-14. Grade 1 hypokalemia was observed in 4 patients, and Grade 1 constipation in 3. We concluded that TJ-14 is sufficiently promising to be examined in a Phase III trial. A randomized controlled trial is currently being planned.